Emergence of Novel Microbial Community Following Natural Disturbance: Paradigm of Ecological Succession and Driving Force of Biodiversity - Ablola, Ferissa B. (International Journal of Scientific Research in Biological Sciences, 2023)
Disturbances are specific events in time that directs changes in resources or alters the physical environment of an ecosystem and, thus, influence community framework and composition. In this systematic review, the impacts of these natural events in the diversity, resistance, resilience and individual unit of the microbial community were synthesized. A comprehensive search following the PRISMA guidelines and eligibility criteria was used to ensure relevance and accuracy of the review. A total of twenty (20) articles were included in this systematic review with eight (8) articles describing the effects of natural disturbance in microbial community in an uncontrolled setting while, the twelve (12) other articles illustrate the influence of simulated disturbance. Four of the most characterized natural disturbance affecting microbial community are volcanic eruption, flooding, pulse/ shock and water column mixing. The conducted statistical analysis (Pearson correlation) revealed that there is a strong correlation (r = 0.97) between the emergence of pioneer organism with the expected inhabitants of the disturbed area. A community can respond to disturbances in different ways regarding composition and function. It can be considered as resistant, that can withstand disturbances without any change or can be tagged as resilient. Overall, the cited studies in this review exemplified the positive impacts of episodic natural disturbances in the ecosystem. Studies showed that these phenomena mediated microbial communities by increasing their production and both their community and phylogenetic diversity.